Trade in International Maritime Services : How Much Does Policy Matter? - Fink, Carsten (World Bank, Washington, DC, 2014)
Maritime transport costs significantly impede international trade. The authors examine why these costs are so high in some countries, and, quantify the importance of two explanations: restrictive trade policies, and private anti-competitive practices. Both matter, they find, but private anti-competitive practices have the greater impact. Trade liberalization, and the breakup of private carrier agreements, would lead to a reduction in average liner transport prices of a third, and cost savings of up to $ 3 billion on goods carried to the United States alone. The policy implications are clear: not only should government policy be further liberalized, but there should be stronger international disciplines on restrictive business practices. The authors propose developing such disciplines in the current round of services negotiations at the World Trade Organization.